Advanced computer simulation approaches for soft matter sciences III - Holm, Christian; Kremer, K.; Bolhuis, Peter G. (Berlin : Springer, 2009)
This book provides short and concise reports on physics and chemistry of polymers, each written by the world renowned experts. The book has the Highest Impact Factor of all publications ranked by ISI within Polymer Science.
Includes bibliographical references and index.
Keywords: Soft condensed matter -- Computer simulation